1980
DOI: 10.1038/bjc.1980.58
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies on caeruloplasmin and iron transferrin in patients with chronic lymphocytic leukaemia

Abstract: Summary.-Whole-blood caeruloplasmin measured by electron spin resonance was studied in 41 patients with chronic lymphocytic leukaemia. The levels were above normal at all stages of the disease, rose with increasing clinical involvement, and were higher in progressive than inactive disease. Whole -blood iron transferrin levels were more variable, and were significantly raised only in patients with marrow failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The level of ceruloplasmin is increased in certain cancers (27)(28)(29) such as prostate cancer (30,31) and after estrogen administration (32,33). Copper-chelating agents (e.g., tetrathiomolybdate) lower ceruloplasmin levels and are potent antiangiogenic agents, but their clinical efficacy in the treatment of metastatic androgen-independent prostate cancer still awaits Each individual phage clone, allowed to circulate for 24 h in tumor-bearing animals, homed specifically to the androgen-independent prostate cancer xenograft.…”
Section: Discussionmentioning
confidence: 99%
“…The level of ceruloplasmin is increased in certain cancers (27)(28)(29) such as prostate cancer (30,31) and after estrogen administration (32,33). Copper-chelating agents (e.g., tetrathiomolybdate) lower ceruloplasmin levels and are potent antiangiogenic agents, but their clinical efficacy in the treatment of metastatic androgen-independent prostate cancer still awaits Each individual phage clone, allowed to circulate for 24 h in tumor-bearing animals, homed specifically to the androgen-independent prostate cancer xenograft.…”
Section: Discussionmentioning
confidence: 99%
“…plasma, and serum are iron transferrin with a signal This value was estimated from a receiver-operating of g Å 4.2 and the copper ceruloplasmin with a signal of g Å 2.049 (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)14). In the pleural effusions, we also observed the signals with g Å 4.2 and 2.049.…”
Section: Origin Of Fe 3/ and Cu 2/ Signals From The Pleuralmentioning
confidence: 92%
“…nance (ESR) 1 method on blood (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Some authors The peak-to-peak height was used as a measure of sighave reported that the patients with the malignant nal intensity, since the signal was confirmed to have diseases such as cancer and Hodgkin's disease had a constant line width and line shape in all the samples.…”
mentioning
confidence: 99%